Nurse performance and quality of care in a selected military health facility - Vidal, Victoria Laigo
Nursing, as a profession, is posed with one of the greatest challenges - the provision of quality nursing care. It is in this realm where we find the essense of nursing responsibility and accountability not only to its clientele, but to the public and the institution as well. Thus, the evaluation of nurse performance and quality of care remains a prime duty of the professional nurse, a primordial concern of nurse administrators and a major role of health institutions.This study deals with the relationship among selected antecedent variables, nurse performance and quality of care. Specifically, it sought to: identify the personal characteristics and work related factors affecting nurse performance at a selected military health facility; assess the levels of nurse performance and quality of care; determine the relationship between the antecedent variables and nurse performance and quality of care; and determine the relationship between nurse performance and quality of care.The conceptual framework of the study is based on the fact that antecedent variables, such as personal characteristics and work related factors may affect the independent and dependent variables. The independent variable or the nurse performance refers to the level of proficiency of the nurse in doing key clinical and administrative skills in the various clinical areas. On the other hand, the dependent variable or the quality of care refers to the kind of attention and care given by a nurse to meet the patient's needs, based on scientific knowledge.The findings of this study pinpoint to areas of importance for the following groups within this military health facility, namely: nurse educators, staff nurses and headnurses, and nurse administrators. For the nurse educators, the strengths and weaknesses of the staff nurses highlighted areas for possible continuing education programs. Particularly, the value of documentation can be reinforced through the proper training program. For the staff nurses, this study underscored the need for constant update in skill proficiency and the need for team effort to arrive at quality nursing care. For the nurse administrators, the evaluation of the nurse performance can provide background data into the individual's level of proficiency. On the other hand, the evaluation of quality of nursing care can serve as depature points for staffing guides. Moreover, this study underscored the need for re-evaluation of the tools currently utilized at this health facility. Lastly, for those interested in related research, the inclusion of the headnurses or a separate study on this particular group offers an area of investigative studies. Furthermore, an evaluation of the nursing audit tool and compentency checklist is a rich area of study.If nursing as a profession is to maintain public trust, it is imperative to evaluate and document not only the competence of nurses, but also the quality of care. For quality care is the right of all patients. These patients are the sole reasons for the existence of health facilities and personnel to include nurses among others. It is therefore the responsibility of these nurses to provide patients with the best possible care. Only then can nursing as a profession truly say that it has answered its accountability not only to the patient, but also to the institution and the public as a whole.